CONDITION OF FOREST PLANTATIONS AND PROSPECTS FOR NATURAL REFORESTATION IN NOVHOROD-SIVERSKE POLISSYA - Demianenko, L. V. (Forestry and Forest Melioration, 2018)
The paper analises fund materials for 5 state forestries of Novhorod-Siverske Polissya for period from 1995 to 2012. The materials represent the areas of the created forest plantations and the area of natural reforestation on agricultural lands. Fund materials concerning the state of forest cultures of Shostkinskiy Forestry for the period from 1998 to 2004 have been studied. Results of research of natural reforestation of Novhorod-Siverske Polissya are brought.